Safety Evaluation of Horizontal Alignment Design Consistency on Rural Two-Lane Highways. Issue 2 (February 2019) - Hamilton, Ian; Himes, Scott; Porter, R. J.; Donnell, Eric
Design consistency in the context of highway and street design refers to the conformance of highway geometry to driver expectancy. Existing design policies provide guidance related to horizontal alignment design consistency. While design consistency has safety implications and is intuitively linked to roadway departure crashes, the authors are only aware of a few studies that sought to link measures of design consistency to safety performance. This study explores relationships between alternative measures of horizontal alignment design consistency and the expected number of roadway departure crashes along horizontal curves on rural, two-lane, two-way roads. The authors analyzed 854 horizontal curves on rural two-lane highways in Indiana and Pennsylvania using data obtained from the SHRP 2 Roadway Information Database (RID) 2.0. Relationships between measures of design consistency and the expected number of roadway departure crashes were explored using a negative binomial regression modeling approach. The results indicate a relationship between the frequency of roadway departure crashes on a study curve and the radii of upstream and downstream curves. The ratio of the length of upstream and downstream tangents relative to a study curve radius was also statistically significant in Pennsylvania. Such findings are intuitive given the concept of design consistency and represent an advancement to existing predictive methods in the AASHTO Highway Safety Manual, which estimate the expected number of crashes on a segment as a function of the characteristics of only that segment.